Development of Basketball Passing Learning Model with A Play Approach to Students Junior High School - Ahmad Rahmadani; Mohd Asmawi; Achmad Sofyan Hanif; Firmansyah Dlis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research and development aims to produce a product of passing basket ball learning models with a play approach to junior high school students and test the effectiveness of these products. The design of this study refers to the research and development model (Research and Development) of Borg and Gall. Broadly speaking, the development steps for the purposes of this research are carried out in 4 stages, namely: preliminary research, model development planning, evaluation evaluation of model revisions, and model implementation. The effectiveness test of the model uses a basketball passing instrument using the t-test one group pretest-posttest design .The results of the effectiveness test were 6.83 when the pre test increased to 10.25 after the post test, an increase of 28.06%. From the results of data analysis it is evident that there was an increase in the results of the pre test and post test for both male and female students. Based on the results of the study, it was proven empirically that the product results in the form of a passing basketball learning model with an approach to play in junior high school students had very good effectiveness and could be implemented.